Screen-detected atrial fibrillation (AF) and "micro-AF" after myocardial infarction in patients 70–82 years and risk of cardiovascular events in the OMEMI trial. (3rd October 2022) - Berge, T; Myhre, P L; Kalstad, A A; Laake, K; Tveit, S H; Onarheim, S; Solheim, S; Seljeflot, I; Arnesen, H; Tveit, A
Abstract: Background: Incident atrial fibrillation (AF) occurs in 5–10% of patients after acute myocardial infarction (AMI) and is associated with adverse outcomes. Guidelines now recommend screening for AF in all elderly patients. However, the yield of extended AF screening after AMI has not been investigated. Short episodes of consecutive irregular supraventricular ectopic beats, entitled "micro-AF", are associated with the development of AF, but the prognostic importance of such findings after an AMI is unknown. Purpose: To investigate the added value of two-week intermittent ECG screening to detect incident AF and "micro-AF" in elderly patients 12 months after an AMI, and its relation to risk of cardiovascular endpoints. Methods: The OMega-3 fatty acids in Elderly patients with Myocardial Infarction (OMEMI) study investigated the effect of Omega-3 fatty acid supplementation on 2-year risk of major cardiovascular events (MACE; non-fatal AMI, stroke, revascularization, or hospitalization for heart failure) in 70–82 years old patients with a recent AMI. All patients had a 12-lead ECG performed at 3, 12 and 24 months. In addition, patients without known AF one year after the index AMI underwent a 2-week period of intermittent 30-second "thumb ECG" screening. Incident AF and "micro-AF" (episodes of ≥3 consecutive irregular supraventricular ectopic beats) were registered and adjudicated by at least two investigators who were blinded to outcome, and the association with risk of MACE was analyzed with logistic regression. Results: Among 1014 patients in the OMEMI trial, 255 (25.1%) had known AF or AF identified at baseline. New-onset AF was detected clinically or at study visits in 39 patients. Screening by 2-week "thumb ECG" was performed in 567 participants without known AF, and identified unknown AF in 4 (0.7%) patients. Another 27 (4.8%) patients had "micro-AF" in at least one ECG recording. In 43 patients with incident AF, 21 (48.8%) experienced a MACE, compared to 114 out of 716 without any AF (15.9%; p<0.001), driven by a higher risk of new AMI or revascularization. Nine (33.3%) patients with "micro-AF" and 63 (12.2%) without "micro-AF" experienced a MACE (p=0.002), explained mostly by a higher risk of hospitalization for heart failure (p<0.001). Using patients without AF and "micro-AF" as reference, "micro-AF" was associated with an intermediate risk of MACE (OR 2.8: 95% CI 1.2–6.4) and new-onset AF with a high risk of MACE (OR 5.3; 95% CI 2.8–10.0). Conclusion: Two-week intermittent ECG screening identified few new cases of new-onset AF, but a substantial number of patients with "micro-AF". "Micro-AF" was associated with an increased risk of major cardiovascular events, albeit with an intermediate risk compared to a higher risk of major cardiovascular events associated with new-onset AF. Funding Acknowledgement: Type of funding sources: None.